Assessing the influence of patient language preference on 30 day hospital readmission risk from home health care: A retrospective analysis. (January 2022) - Squires, Allison; Ma, Chenjuan; Miner, Sarah; Feldman, Penny; Jacobs, Elizabeth A.; Jones, Simon A.
Abstract: Background: In home health care, language barriers are understudied. Language barriers between patients and providers are known to affect a variety of patient outcomes. How a patient's language preference influences hospital readmission risk from home health care has yet to be determined. Objective: To determine if home care patients' language preference is associated with their risk for hospital readmission from home health care within 30 days of hospital discharge. Design: Retrospective cross-sectional study of hospital readmissions from an urban home health care agency's administrative records and the national electronic home health care record for the United States, captured between 2010 and 2015. Setting: New York City, New York, USA. Participants: The dataset comprised 90, 221 post-hospitalization patients and 6.5 million home health care visits. Methods: First, a Chi-square test was used to determine if there were significant differences in crude readmission rates based on language group. Inverse probability of treatment weighting was used to adjust for significant differences in known hospital readmission risk factors between to examine all-cause hospital readmission during a home health care stay. The final matched sample included 87, 561 patients with a language preference of English, Spanish, Russian, Chinese, or Korean. English-speaking patients were considered the comparison group to the non-English speaking patients. A Marginal Structural Model was applied to estimate the impact of non-English language preference against English language preference on rehospitalization. The results of the marginal structural model were expressed as an odds ratio of likelihood of readmission to the hospital from home health care. Results: Home health patients with a non-English language preference had a higher hospital readmission risk than English-speaking patients. Crude readmission rate for the limited English proficiency patients was 20.4% (95% CI, 19.9–21.0%) overall compared to 18.5% (95% CI, 18.7–19.2%) for English speakers ( p < 0.001). Being a non-English-speaking patient was associated with an odds ratio of 1.011 (95% CI, 1.004–1.018) in increased hospital readmission rates from home health care ( p = 0.001). There were also statistically significant differences in readmission rate by language group ( p < 0.001), with Korean speakers having the lowest rate and Spanish speakers having the highest, when compared to English speakers. Conclusions: People with a non-English language preference have a higher readmission rate from home health care. Hospital and home healthcare agencies may need specialized care coordination services to reduce readmission risk for these patients. Tweetable abstract: A new US-based study finds that home care patients with language barriers are at higher risk for hospital readmission.